Off-Pump Transapical Removal of An Embolized Transcatheter Aortic Valve. Issue 3 (May 2017) - Taylor, Lauren J.; Raval, Amish N.; Osaki, Satoru; Kohmoto, Takushi; Lozonschi, Lucian
Transcatheter aortic valve replacement is a less invasive alternative for high-risk patients. However, valve embolization is a rare but dreaded complication. We report the successful off-pump retrieval of an embolized valve after transfemoral transcatheter aortic valve replacement through a left anterior thoracotomy. We maintained the embolized valve on the guidewire and snared it using a transapical approach. We then deployed a valve in an adequate position to ensure hemodynamic stability before transapical removal of the embolized valve. Transapical exteriorization of the femoral guidewire offers additional support, particularly in patients with a horizontal aortic annulus.